Completing the GATT Uruguay Round renewed multilateralism or a world of regional trading blocs? - Hopkinson, Nicholas (HMSO LondonGB, 1992)
Emphasizes the need for the Uruguay Round of Trade Negotiations to be completed. Highlights some of the consequences that would result if these negotiations are not quickly concluded.